World War I and World War II: Their Effects on the Islamic World and Afghanistan - Hamid, Nisar Ahmad; Asim, Esmatullah (Integrated Journal for Research in Arts and Humanities, 2024)
The tremendous effects that World War I and World War II had on the Islamic world are investigated in this research, with a particular focus on Afghanistan. The aftermath of World War I resulted in the breakup of empires, most notably the Ottoman Empire, as well as the restructuring of political boundaries. The study aims to explore and analyze the far-reaching impacts of World War I and World War II on the Islamic world, with a particular focus on Afghanistan. The study seeks to examine how these global conflicts reshaped political, social, and economic dynamics in Muslim-majority regions, leading to the disintegration of empires, the rise of nationalism, and the realignment of power structures. The significance of this study lies in the fact that it shades light on a relatively unexplored facet of world history, namely the manner in which the Islamic world, and Afghanistan in particular, was impacted by the two World Wars. Specifically, it sheds light on the growth of nationalism, decolonization, and geopolitical competition, all of which played a role in shaping the position of Afghanistan, Central Asia, and the Middle East within the global system. This work employs the doctrinal research methodology along with descriptive, explanatory, and analytical research approaches. It is worth mentioning that this research study is entirely based on library sources. Most of the sources are reputable and trustworthy textbooks, scholarly published and unpublished journal articles, law reports, and online websites related to the research area. One of the main findings is Both World Wars accelerated the disintegration of Islamic empires, notably the Ottoman Empire, and paved the way for European colonial powers to carve out new territories in the Middle East, Africa, and South Asia. Afghanistan’s strategic position made it vulnerable to foreign influence, particularly from Britain and Russia. After World War I, Afghanistan gained greater autonomy, but it became a battleground for influence between the Soviet Union and the West following World War II, especially during the Cold War. It is recommended that further research and documents are needed the Islamic world’s experience during both World Wars, which has often been overlooked in global history. Incorporating these perspectives into academic curricula could help reshape understanding of global conflicts from a non-Western perspective.